(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The goal of this study is to determine the best strategy for marketing baby product in India through the creation of a planning model. A methodology based on questionnaires is used to collect information for the study on the preferences, habits, and traits of Indian parents and caregivers. Testing hypotheses, and producing visualizations like pie charts and bar graphs are all parts of the data analysis process (Agnihotri, 2015). The study’s findings include insightful information on the target audience’s demographics, preferred media outlets, key advertising elements, likelihood of engagement with advertisements, exposure to baby product commercials, and variables impacting buying behavior